ASUHAN KESEHATAN GIGI DAN MULUT IBU HAMIL PADA NY MA DENGAN KASUS GINGIVITIS - Azizah, Dita Nur; Utami, Ulfah; Nurjanah, Neneng; Marah Laut, Deru (Poltekkes Kemenkes Bandung, 2024)
Pregnancy is a common event in a woman's life that involves physiological and hormonal changes. The risk of dental disease increases during pregnancy, due to several factors such as an increased gag reflex and behavioral changes such as poor oral hygiene that can increase the risk of tooth decay and periodontal disease. Gingivitis is a periodontal disease characterized by red gums and is caused by plaque and other factors including hormonal factors that often occur during pregnancy. The purpose of this study was to determine the results of oral health care in pregnant women. This research method is a case report with the concept of oral health care which consists of the process of assessment, diagnosis, planning, implementation and evaluation. After the examination, the diagnosis was stated that there were 5 basic human needs that were not met. Implementation carried out on clients is cleaning tartar, ART filling, counseling with the Chair Side Talk method, oral physiotherapy and referral to the dentist for further treatment. The evaluation results show that there are 3 basic human needs that have been achieved and 2 basic human needs that have only been partially fulfilled, so the 8 basic human needs of clients have not been fully met.